2008
DOI: 10.1203/pdr.0b013e3181659759
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Therapy in Preterm Infants Developing Bronchopulmonary Dysplasia: Effect on Pulmonary Surfactant Disaturated-Phosphatidylcholine Kinetics

Abstract: ABSTRACT:The role of corticosteroid in severe bronchopulmonary dyplasia (BPD) is still debated. Scanty data are available on the corticosteroids effect on surfactant metabolism. Our objective was to compare surfactant kinetics in preterm infants with developing BPD, before and after dexamethasone (DEXA) treatment. Twenty-eight studies were performed in 14 preterm infants (birth weight 786 Ϯ 192 g, gestational age 26 Ϯ 1 wk) on high ventilatory setting, before (age 22 Ϯ 11 d) and after (age 33 Ϯ 11 d) DEXA.13 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…To further explain these findings, we used deuterated water as metabolic precursor of DSPC to measure surfactant DSPC synthesis and secretion of the I and NI lungs, together with total lungs DSPC turnover (7,10). Below we briefly comment on the effect of DSPC metabolism on lung homogenate DSPC pools and BALF DSPC pools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further explain these findings, we used deuterated water as metabolic precursor of DSPC to measure surfactant DSPC synthesis and secretion of the I and NI lungs, together with total lungs DSPC turnover (7,10). Below we briefly comment on the effect of DSPC metabolism on lung homogenate DSPC pools and BALF DSPC pools.…”
Section: Discussionmentioning
confidence: 99%
“…Study mice (naïve controls and HCl treated mice, n ϭ 4 per control or experimental group) received an intraperitoneal dose of 1 ml/kg 10% (v/v) of deuterated water (Cambridge Isotope Laboratories, Andover, MA) to assess DSPC-palmitate synthesis and secretion. Animals were killed at 4,8,10,12,20, and 24 h after isotope administration, corresponding to 22,26,28,30,38, and 42 h after HCl injury. The age matched naïve control animals received the intraperitoneal dose of deuterated water and were killed at 4,8,10,12,20, and 24 h after isotopes administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 C-palmitate enrichment was measured by gas-chromatography-mass-spectrometry (GC-MS, 6890N-5973 inert, Agilent Technologies, Milan, Italy). Results were expressed as mole percent excess referring to a calibration curve (31,38).…”
Section: Methodsmentioning
confidence: 99%
“…However in 1998, Griese and Westerburg [95] demonstrated that the inhibition of surfactant function by proteins leaked into the airspaces did not play a major role during recovery from RDS, so they concluded that endogenous remodeling of surfactant might be of greater relevance. More recently, dexamethasone treatment not only significantly reduced inflammatory markers but also significantly increased the alveolar surfactant desaturated phosphatidylcholine pool in mechanically ventilated preterm infants with severe respiratory failure who were at high risk for developing BPD [96]. …”
Section: Pathophysiologic Factors In Bpdmentioning
confidence: 99%